(untitled) (Bon Voyage, 2023)
Did rhetoric naturally evolve from the inherent power and potential of language, or were specific political and cultural conditions instrumental in driving its development in classical Greece? This paper explores this question by adopting a historical approach to rhetoric and a rhetorical approach to history. It draws on the perspectives of sophists such as Gorgias, the anonymous author of “Dissoi Logoi,” and Isocrates, as well as the rhetorical philosophical orientations of Plato and Aristotle. In conducting this study, I employ a methodological review approach that relies on the scholarship of rhetoric and rhetorical history and critically analyse available sources and the arguments developed in the field. Through this approach, I argue that the emergence of rhetoric in classical times was prompted by several exigent factors, including humanism, democracy, education, literacy, and legal practices. Therefore, theorizing and practicing rhetoric beyond the cultural-political context is inherently partial and incomplete.